2021
DOI: 10.3390/jcm10204669
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Repetitive Transcranial Magnetic Stimulation in Fibromyalgia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: This article aimed to investigate the efficacy of repetitive transcranial magnetic stimulation (rTMS) in fibromyalgia. The PubMed, Medline, Cochrane Library, and Web of Science databases were searched for articles published through 14 August 2021. We enrolled only randomized controlled trials. The Cochrane Collaboration risk of bias tool was used for quality assessment. Outcomes were analyzed as standardized mean differences (SMDs) with 95% CIs. The beta coefficient and p value were adopted for meta-regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 60 publications
2
38
0
3
Order By: Relevance
“…DLPFC directly promotes or inhibits pain through coordination with these brain regions or through modulating the activity of pain descending inhibition pathways ( 31 ). Therefore, DLPFC-rTMS was able to reduce pain sensation, as supported by several recent studies, like spinal cord injury ( 12 ), migraine ( 13 ) and fibromyalgia ( 14 ). In this study, we hypothesized that DLPFC-rTMS may also be effective in the treatment of cancer pain and thus conducted this trial.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…DLPFC directly promotes or inhibits pain through coordination with these brain regions or through modulating the activity of pain descending inhibition pathways ( 31 ). Therefore, DLPFC-rTMS was able to reduce pain sensation, as supported by several recent studies, like spinal cord injury ( 12 ), migraine ( 13 ) and fibromyalgia ( 14 ). In this study, we hypothesized that DLPFC-rTMS may also be effective in the treatment of cancer pain and thus conducted this trial.…”
Section: Discussionsupporting
confidence: 57%
“…Usually, low frequency (< 1Hz) stimulation has an inhibitory effect on the brain, while high frequency (> 5Hz) stimulation excite neurons ( 11 ). It has been reported that rTMS relieves various types of pain, such as neuropathic pain after spinal cord injury, stroke or postoperative of trigeminal nerve ( 12 ), migraine ( 13 ), fibromyalgia ( 14 ) and chronic musculoskeletal pain ( 15 ). Even less clinical study has been done on the application of rTMS in patients with cancer pain.…”
Section: Introductionmentioning
confidence: 99%
“…Fibromyalgia syndrome (FMS) is a severe widespread pain associated with sleep disorders and cognitive dysfunction [ 54 ]. Two recent meta-analyses concluded that high-frequency rTMS over the left M1 effectively relieved pain and improved the quality of life in patients with FMS [ 56 , 57 ]. The improvement in FMS symptomology was associated with changes in resting-state connectivity and metabolism in sensory, affective, and cognitive brain processing areas, as shown in fMRI [ 58 ] and PET scans [ 59 ].…”
Section: Painmentioning
confidence: 99%
“…In two recent meta-analyses, fatigue severity scales (FSS) did not show significant improvement following rTMS in fibromyalgia syndrome (FMS) patients [ 56 , 57 ]. However, neither of these studies conducted a subgroup analysis on the effect of targeting M1 and only included FSS as an outcome measure for fatigue, which was used in a single M1-rTMS study.…”
Section: Fatiguementioning
confidence: 99%
See 1 more Smart Citation